2017
DOI: 10.5858/arpa.2016-0478-oa
|View full text |Cite
|
Sign up to set email alerts
|

Do Infection Patterns of Human Papillomavirus Affect the Cytologic Detection of High-Grade Cervical Lesions on Papanicolaou Tests?

Abstract: - Our findings suggest that multigenotypic or non-16/18 hrHPV infections often produce deceptive lower-grade cytomorphology, which could result in underdiagnosis and delay of treatment. The HPV infection patterns may offer unrecognized benefit beyond HPV genotyping and should be considered during clinical risk evaluation of women with lower-grade cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The most recent interesting paper published by Samimi et al reported a problem with a cytological pattern detection of HPV infection. The authors concluded the HSIL cytological pattern might be obscured in cases of multigenotype hrHPV infection and in fact, true HSIL cases could mimic unequivocal Pap patterns (ASC-US, ASC-H, LSIL) [25]. In our cohort, we found only one biopsy, which confirmed Semimi's thesis.…”
Section: Discussionsupporting
confidence: 85%
“…The most recent interesting paper published by Samimi et al reported a problem with a cytological pattern detection of HPV infection. The authors concluded the HSIL cytological pattern might be obscured in cases of multigenotype hrHPV infection and in fact, true HSIL cases could mimic unequivocal Pap patterns (ASC-US, ASC-H, LSIL) [25]. In our cohort, we found only one biopsy, which confirmed Semimi's thesis.…”
Section: Discussionsupporting
confidence: 85%
“…A study investigating detectability of biopsyconfirmed high-grade cervical lesions by pap-smear reported that false low-grade cytomorphology rates were higher in non-16/18 hrHPV and mixed hrHPV infected women than HPV 16/18 infected women. In light of this the authors suggested that diagnosis-treatment approach might be delayed due to increased pap test underdiagnosis rates (Samimi at al., 2018). Another problem is the lack of annual co-test follow-up compliance by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although data is limited and conflicting on this issue, it is possible that HPV 16 associated ≥CIN2 is more likely to be referred for colposcopy using standard management guidelines than is ≥CIN2 associated with other HPV genotypes [33,34]. ≥CIN2 lesions with HPV 16/18 are more likely accompanied by high-grade cytologic findings than ≥CIN2 lesions associated with other genotypes [35]. Moreover, lesion size is a determinant of the performance of both colposcopy and cervical biopsy; and HPV 16 associated ≥CIN2 lesions develop more rapidly than ≥CIN2 lesions associated with other HPV types [36,37].…”
Section: Discussionmentioning
confidence: 99%